Relations of some personality traits and characteristics of sportsmen with the level of sports anxiety - Velikic, D.; Kneževic, J.; Rodic, N. (SportLogia, 2014)
Sports anxiety, as a kind of anxiety, drives a tendency to evaluate the competition situations as threatening, and in response to this situation, there is an anxious state. As the previous research results show the link between anxiety levels and achievement, research problem is whether there is a connection between the personality traits of athletes with a degree of anxiety in athletes, as well as whether there are differences in the level of anxiety in relation to sex of athletes, type of sports and the level of success in sport. The goal of this research is to improve understanding of the personal and situational factors associated with anxiety in athletes. The starting point was the multidimensional theory of anxiety that distinguishes somatic component of anxiety, cognitive component and confidence. The study included 90 athletes who were asked to judge the degree of sports anxiety using the CSAI-2 scale and personality traits (VP+2). The findings confirm the personality traits as predictors of somatic anxiety, with the aggressiveness being a significant predictor of somatic anxiety. Neuroticism, openness and aggressiveness emerged to be the predictors of cognitive anxiety and conscientiousness, openness and aggressiveness as predictors of sport confidence.